Image-based cataract diagnosis - Fung, Daniel Kai Xiang (Nanyang Technological University, 2023)
Cataracts, the clouding of the eye's lens, poses a global health challenge as a leading cause of visual impairment. There is a need for improved cataract screening and diagnosis as traditional diagnosis methods are limited in access, involving expensive equipment, and requiring great expertise.